Impact of presenting patient characteristics on surgical complications and morbidity in early onset scoliosis. (April 2019) - Segreto, Frank A.; Vasquez-Montes, Dennis; Bortz, Cole A.; Horn, Samantha R.; Diebo, Bassel G.; Vira, Shaleen; Kelly, John J.; Stekas, Nicholas; Ge, David H.; Ihejirika, Yael U.; Lafage, Renaud; Lafage, Virginie; et al.
Highlights: EOS patients with musculoskeletal conditions more likely to have renal anomalies. Epilepsy and pulmonary failure were risks for patients with pulmonary disease. Clustered neurologic and pulmonary anomalies increased mortality risk. Clustered musculoskeletal and cardiovascular anomalies increased length of stay. Abstract: This study sought to assess comorbidity profiles unique to early-onset-scoliosis (EOS) patients by employing cluster analytics and to determine the influence of isolated comorbidity clusters on perioperative complications, morbidity and mortality using a high powered administrative database. The KID database was queried for ICD-9 codes pertaining to congenital and idiopathic scoliosis from 2003, 2006, 2009, 2012. Patients <10 y/o (EOS group) were included. Demographics, incidence and comorbidity profiles were assessed. Comorbidity profiles were stratified by body systems (neurological, musculoskeletal, pulmonary, cardiovascular, renal). K-means cluster and descriptive analyses elucidated incidence and comorbidity relationships between frequently co-occurring comorbidities. Binary logistic regression models determined predictors of perioperative complication development, mortality, and extended length-of-stay (≥75th percentile). 25, 747 patients were included (Age: 4.34, Female: 52.1%, CCI: 0.64). Incidence was 8.9 per 100, 000 annual discharges. 55.2% presented with pulmonary comorbidities, 48.7% musculoskeletal, 43.8% neurological, 18.6% cardiovascular, and 11.9% renal; 38% had concurrent neurological and pulmonary. Top inter-bodysystem clusters: Pulmonary disease (17.2%) with epilepsy (17.8%), pulmonary failure (12.2%), restrictive lung disease (10.5%), or microcephaly and quadriplegia (2.1%). Musculoskeletal comorbidities (48.7%) with renal and cardiovascular comorbidities (8.2%, OR: 7.9 [6.6–9.4], p < 0.001). Top intra-bodysystem clusters: Epilepsy (11.7%) with quadriplegia (25.8%) or microcephaly (20.5%). Regression analysis determined neurological and pulmonary clusters to have a higher odds of perioperative complication development (OR: 1.28 [1.19–1.37], p < 0.001) and mortality (OR: 2.05 [1.65–2.54], p < 0.001). Musculoskeletal with cardiovascular and renal anomalies had higher odds of mortality (OR: 1.72 [1.28–2.29], p < 0.001) and extLOS (OR: 2.83 [2.48–3.22], p < 0.001). EOS patients with musculoskeletal conditions were 7.9x more likely to have concurrent cardiovascular and renal anomalies. Clustered neurologic and pulmonary anomalies increased mortality risk by as much as 105%. These relationships may benefit pre-operative risk assessment for concurrent anomalies and adverse outcomes. Level of Evidence : III – Retrospective Prognostic Study.